Linking sensitivity to limited distribution: the case of free choice - Giannakidou, Anastasia (Proceedings of the Amsterdam Colloquium, 1997)
In this paper I propose an analysis of free choice indefinites (FCIs) in Greek as polarity items. The primary goal is to connect the constraints on the distribution of FCIs to their semantics, in favor of the more general argument that it is sensitivity that determines limited distribution in polarity items. First, I establish that the FC paradigm is distinct from negative polarity. Next, I propose a semantics of FCIs as attributive indefinites. Attributiveness is a modal feature imposing the requirement that FCIs be interpreted with respect to a set of epistemic i(dentity)- alternatives to the world of evaluation wo. This interpretative requirement fails to be satisfied in episodic contexts, i.e contexts which involve event closure, FCIs will thus be ungrammatical there. By contrast, FCIs will be grammatical in contexts where the event variable is bound by some operator or absent altogether (habitual/generic sentences and individual-level predicates). The anti-episodicity requirement is captured in the form of an anti-licensing condition, hence allowing for anti-licensing as a theoretically available option for well-formedness conditions on certain PIs. This condition can be shown to account directly not only for the facts in Greek, but also for FCIs in (at least) Spanish and Catalan.